2019
DOI: 10.1115/1.4043548
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Additively Manufactured Cooled Ultra Compact Combustor Vane

Abstract: The ultra compact combustor (UCC) aims to increase the thrust-to-weight ratio of an aircraft gas turbine engine by decreasing the size, and thus weight, of the engine’s combustor. The configuration of the UCC as a primary combustor enables a unique cooling scheme to be employed for the hybrid guide vane (HGV). A previous effort conducted a computational fluid dynamics (CFD) analysis that evaluated whether it would be possible to cool this vane by drawing in freestream flow at the stagnation region of the airfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Cottle et al 25 added a set of injection plates and baffles to an HGC with a diffuser to control the directions and ratios of the core and secondary streams. Subsequently, Bohan et al 26,27 designed a cooling scheme by designing holes to form a cooling film and hence mitigate the localized overheating problem of the HGC. Zhang et al 6 designed an asymmetric combustion chamber, and the experimental results showed that the combustion efficiency was greater than 94%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cottle et al 25 added a set of injection plates and baffles to an HGC with a diffuser to control the directions and ratios of the core and secondary streams. Subsequently, Bohan et al 26,27 designed a cooling scheme by designing holes to form a cooling film and hence mitigate the localized overheating problem of the HGC. Zhang et al 6 designed an asymmetric combustion chamber, and the experimental results showed that the combustion efficiency was greater than 94%.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Bohan et al , designed a cooling scheme by designing holes to form a cooling film and hence mitigate the localized overheating problem of the HGC. Zhang et al designed an asymmetric combustion chamber, and the experimental results showed that the combustion efficiency was greater than 94%.…”
Section: Introductionmentioning
confidence: 99%
“…As well known, gas turbines are numerously used to convert energy of combustio gases into mechanical work. [1][2][3][4][5][6] One main goal in gas turbine engine development is to increase its thermodynamics efficiency, of which the turbine inlet temperature plays a very important role. Evidently, this temperature should not exceed the allowable design temperature of metal parts.…”
Section: Introductionmentioning
confidence: 99%